Hokkaido birth cohort study on environment and children's health: cohort profile 2021 - Reiko Kishi; Atsuko Ikeda-Araki; Chihiro Miyashita; Sachiko Itoh; Sumitaka Kobayashi; Yu Ait Bamai; Keiko Yamazaki; Naomi Tamura; Machiko Minatoya; Rahel Mesfin Ketema; Kritika Poudel; Ryu Miura; et al. (Komiyama Printing Co. Ltd, 2021)
Abstract Background The Hokkaido Study on Environment and Children's Health is an ongoing study consisting of two birth cohorts of different population sizes: the Sapporo cohort and the Hokkaido cohort. Our primary objectives are to (1) examine the effects that low-level environmental chemical exposures have on birth outcomes, including birth defects and growth retardation; (2) follow the development of allergies, infectious diseases, and neurobehavioral developmental disorders, as well as perform a longitudinal observation of child development; (3) identify high-risk groups based on genetic susceptibility to environmental chemicals; and (4) identify the additive effects of various chemicals, including tobacco. Methods The purpose of this report is to provide an update on the progress of the Hokkaido Study, summarize recent results, and suggest future directions. In particular, this report provides the latest details from questionnaire surveys, face-to-face examinations, and a collection of biological specimens from children and measurements of their chemical exposures. Results The latest findings indicate different risk factors of parental characteristics on birth outcomes and the mediating effect between socioeconomic status and children that are small for the gestational age. Maternal serum folate was not associated with birth defects. Prenatal chemical exposure and smoking were associated with birth size and growth, as well as cord blood biomarkers, such as adiponectin, leptin, thyroid, and reproductive hormones. We also found significant associations between the chemical levels and neuro development, asthma, and allergies. Conclusions Chemical exposure to children can occur both before and after birth. Longer follow-up for children is crucial in birth cohort studies to reinforce the Developmental Origins of Health and Disease hypothesis. In contrast, considering shifts in the exposure levels due to regulation is also essential, which may also change the association to health outcomes. This study found that individual susceptibility to adverse health effects depends on the genotype. Epigenome modification of DNA methylation was also discovered, indicating the necessity of examining molecular biology perspectives. International collaborations can add a new dimension to the current knowledge and provide novel discoveries in the future.